1992
DOI: 10.1113/jphysiol.1992.sp019225
|View full text |Cite
|
Sign up to set email alerts
|

A persistent sodium current in rat ventricular myocytes.

Abstract: SUMMARY1. The tight seal, whole-cell, voltage-clamp technique was used to record currents from single ventricular myocytes acutely dissociated from adult rat hearts. Subtraction of currents recorded in the presence and absence of tetrodotoxin (TTX, 50 /SM) revealed a small, persistent, inward current following a much larger, transient, inward current.2. Both currents were sodium currents because they reversed close to the sodium equilibrium potential and were depressed when choline was substituted for extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
1
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 18 publications
5
147
1
1
Order By: Relevance
“…Another set of voltagedependent channels might be involved. However, although channels which will support long lasting depolarizations have been demonstrated in cardiac muscle (Saint et al 1992), they have not been demonstrated in antral smooth muscle cells (Noack et al 1992). The alternative possibility is that the regenerative component arises from the regenerative release of Ca¥ from an internal store (Fabiato & Fabiato, 1975) and this activates a set of channels which causes an increase in the net positive internal charge (see as examples Pacaud & Bolton, 1991;Large & Wang, 1996;Hashitani, et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Another set of voltagedependent channels might be involved. However, although channels which will support long lasting depolarizations have been demonstrated in cardiac muscle (Saint et al 1992), they have not been demonstrated in antral smooth muscle cells (Noack et al 1992). The alternative possibility is that the regenerative component arises from the regenerative release of Ca¥ from an internal store (Fabiato & Fabiato, 1975) and this activates a set of channels which causes an increase in the net positive internal charge (see as examples Pacaud & Bolton, 1991;Large & Wang, 1996;Hashitani, et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…3, 5, and 7). The persistent I Na current has been observed in adult mammalian ventricular cardiomyocytes (14), and hypoxia has been shown to enhance its amplitude (5). Increased Na ϩ influx during hypoxia increases intracellular Na ϩ concentration ([Na ϩ ] i ), which in turn activates the reversal mode of the Na ϩ /Ca 2ϩ exchanger so that intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) level increases as well.…”
Section: Discussionmentioning
confidence: 99%
“…How the mutant L409C/A410W produces an inactivationdeficient channel, which it does (14), must be different from that produced by the inactivation-dependent mutant IFMQ3. It has been postulated that the mutant L409C/A410W composes part of the receptor site for the docking of the inactivation particle (15).…”
mentioning
confidence: 99%
“…+ currents in neurons Persistent (noninactivating) Na + currents flowing at subthreshold potentials have been recorded in various tissues such as frog node of Ranvier (19), cat lumbar motoneurons (20), rat and guinea pig hippocampal neurons (21), rat ventricular myocytes (22), rat optic nerve axons (23), rat and cat cortical pyramidal neurons (24), guinea pig trigeminal motoneurons (25), rat dorsal root ganglion (DRG) neurons (26) and guinea pig cerebellar Purkinje cells (27).…”
Section: -1 Persistent Namentioning
confidence: 99%